Peran Guru PAI dan Orang Tua dalam Mengembangkan Sikap Spiritual Siswa di MTSN 3 Kota Surabaya - Najah, Faizun; Rahman, Aulia (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
This study aims to describe and analyze the role of Islamic Religious Education (PAI) teachers and parents in developing students' spiritual attitudes at MTsN 3 Surabaya City. This study uses a descriptive qualitative approach to understand the role of Islamic Religious Education (PAI) teachers and parents in developing students' spiritual attitudes at MTsN 3 Surabaya City, by collecting data through interviews, observations, and documentation. The researcher acted as the main instrument, conducting direct interactions with informants selected by purposive sampling, including teachers, students, and parents. Data analysis followed the Miles and Huberman model, with the validity of the data checked through triangulation of sources, methods, and theories to ensure the consistency and integrity of the research results. The results showed that Islamic Religious Education (PAI) teachers at MTsN 3 Surabaya City play a central role in the formation of students' spiritual attitudes as teachers, mentors, and role models who practice spiritual values. Parents also have a significant role as planners and mentors, creating spiritual habits at home and encouraging children to be consistent in their religion. Collaboration between teachers and parents creates harmony between education at school and at home, strengthening students' spiritual development. Students showed positive achievements in spiritual attitudes, such as performing religious services consistently, doing charity without coercion, and being patient in completing assignments. These findings indicate that cooperation between Islamic Religious Education teachers and parents has succeeded in forming good spiritual attitudes among students.